The impact of Industrial subcontracting on the promotion of small ‎and ‎medium enterprises- France experience- - ait said, fouzi; BENLAGHA, Mohamed Reda (Journal of Excellence for Economics and Management Research, 2023)
The research focuses on the role of the Industrial subcontracting strategy to ‎‎‎encourage small and medium-sized sub-contracting. The main hypothesis is that this ‎‎‎strategy did not liberate subcontracting enterprises from their dependence on the ‎‎ordering enterprises. This study aims to highlight on Industrial subcontracting as a ‎‎strategy to improve the ‎performance of small and medium enterprises. For this, we ‎‎relied on the descriptive and analytical ‎approach. To understand the subject more, we supported our study with a set of recent statistics in this field, which pertain to the countries of the European Union, where the analyzes clearly showed that the subcontracting strategy contributes to the intensification of the local industrial fabric and thus achieves economic development.